2002
DOI: 10.1177/0091270002424002
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sampling Strategy to Predict AUC of the CYP3A Phenotyping Probe Midazolam in Adults: Application to Various Assay Techniques

Abstract: Midazolam clearance is used to phenotype hepatic CYP3A activity but requires multiple plasma samples following a single intravenous dose. The authors evaluated the use of a limited sampling scheme, using different assay techniques to determine the reproducibility of such a strategy in estimating midazolam AUC. Seventy-three healthy adults received midazolam as a single intravenous bolus dose. At least eight plasma samples were collected from each subject and were assayed using either LC/MS/MS or electron captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 28 publications
0
67
0
Order By: Relevance
“…Earlier studies by various groups, including our own, established LSS for midazolam AUC mainly in the uninhibited state of CYP3A4. 9,36 The only other study that examined the use of LSS for midazolam in an inhibited as well as induced states for CYP 3A reported the successful use of a single time point at 4 hours, close to the harmonic mean of the MRT, 3.5 hours. 8 Although the harmonic mean of the MRT may be a good guide for the selection of an optimal sampling time for single-point LSS based on statistical moment theory, the case was different in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies by various groups, including our own, established LSS for midazolam AUC mainly in the uninhibited state of CYP3A4. 9,36 The only other study that examined the use of LSS for midazolam in an inhibited as well as induced states for CYP 3A reported the successful use of a single time point at 4 hours, close to the harmonic mean of the MRT, 3.5 hours. 8 Although the harmonic mean of the MRT may be a good guide for the selection of an optimal sampling time for single-point LSS based on statistical moment theory, the case was different in this study.…”
Section: Discussionmentioning
confidence: 99%
“…LSS has been used to estimate pharmacokinetic parameters for therapeutic agents 9 -11 or to monitor the drug administration regimen, 12,13 and also to predict CYP3A activity using a phenotyping probe drug. 9,14 However, it is still unclear whether the predictive equation for MDZ clearance using a LSS generated from a randomized population in which Laboratory Animals 2009; 43: 284 -290 hepatic CYP3A may have been inhibited to varying degrees could be used to estimate CYP3A-dependent metabolism in the rat liver. Resolving this question is a valuable contribution to metabolism research.…”
mentioning
confidence: 99%
“…20 In contrast, another study evaluated IV midazolam LSMs and reported acceptable precision and bias when comparing LC/MS/ MS and electron capture gas chromatography assays. 17 Consequently, the magnitude and extent to which different bioanalytical assays contribute to findings in this study is unknown but may provide a partial explanation for our findings.…”
Section: Discussionmentioning
confidence: 85%
“…Bias and precision were assessed by acceptable limits of percent mean prediction error (%MPE) 25 to 5%, percent mean absolute error (%MAE) # 10%, and percent root mean square error (%RMSE) # 15%. 4,16,17 …”
Section: Blood Sample Collection and Assaymentioning
confidence: 99%